Policy transfer as a form of prospective policy evaluation: challenges and recommendations - Mossberger, Karen; Wolman, Harold (2003)
This article focuses on policy transfer as a form of prospective policy analysis, which we define as policy makers' attempts to assess the effect of a policy or program before it is put in place. Despite a burgeoning literature on cross-national policy transfer, there has been little systematic comparison of cases to identify either common problems or potential strategies in the practice of policy transfer. This article sets forth a rational model of policy transfer and examines, in light of that model, case studies of cross-national policy transfer spanning different policy domains. Taking into account the constraints faced by policy makers, we relax standard rational decision-making criteria and make recommendations for improving the process of policy transfer as a form of prospective policy evaluation. - Reproduced.
Keywords: Decision making; Policy making